A Comparative Anatomical Study of the Grapevine, Shoot and Cane: II: Periderm and Secondary Phloem - Swanepoel, J. J.; De La Harpe, A. C.; Orffer, C. J. (South African Journal of Enology and Viticulture, 2017)
The taxonomic value of ten periderm and secondary phloem features of canes of different grapevine species was investigated. A scatter diagram showed that with few exceptions the American cultivars have a larger periderm with smaller secondary phloem, while the reverse was true for European cultivars. Crosses tend to cluster with one of their parents. It has been found that the largest intercultivar variation occurs at either the middle of the shoot length or the ventral sides of the basal part of the shoots.